Effectiveness training type on body composition and metabolic parameters in adolescents with obesity: review - Guilarducci Costa, Thalles; Rodrigues, Louise; Ramos-Urrea, Carlos (Archivos Latinoamericanos de Nutrición (ALAN), 2021)
No systematic reviews had analyzedthe most effective training for adolescents with obesity, thus, the aim of our review was to understand whether aerobic, resistance, or combinate, is appropriate for improving body composition, and factors associated with obesity in adolescents. We followed PRISMA methods, in the Pubmed, SCOPUS, and Web of Science databases, using the terms Obesity, teenager, fat mass, body mass index, body mass, intervention, aerobic, resistance, training and physical activity. Subsequently, titles and abstracts were read to filter the articles. Of the 3585 results found, 10 articles were selected with protocols of 3 to 4 weekly training sessions of 15 to 60 minutes, with interventions of 4 to 12 weeks. All types of training were beneficial for anthropometric and biochemical improvement, only resistance training (RT) has a significant difference for muscle mass compared to aerobic training (AT). Even though of the small number of studies with this type of comparison, it is still unclear which type of training is better or whether the two done concurrently would be a better alternative. According to our findings adolescents who want to maximize the effect of exercise on anthropometric variables should ideally perform aerobic and endurance exercises, but significant benefit can be achieved through any type of exercise, and if it were to have a significant differentiation within muscle mass the resistance exercise may be ideal to achieve this goal. En este artículo de revisión, fue analizado cual es el método de entrenamiento que es más efectivo para adolescentes con obesidad, de allí, a que nuestro objetivo en esta revisión es definir cual de los protocolos de entrenamiento (aeróbico, de resistenciao combinado) es mas apropiado para mejorar la composición corporal y otros factores asociados con la obesidad en adolescentes. Siguiendo los métodos de PRISMA se realizóla búsqueda en las bases de datos de, Pubmed, SCOPUS, y Web os Science, utilizando términos de obesidad, adolescentes, masa grasa, índice de masa corporal, masa corporal, intervención, ejercicio aeróbico, ejercicio de resistencia, ejercicio combinado y actividad física, subsecuentemente se leyeron títulos y resúmenes para filtrar los artículos. De los 3585 artículos encontrados, 10 artículos fueron seleccionados con protocolos de 3 a 4 días a la semana, donde cada sesión era de 15 a 60 minutos, con intervenciones entre 4 y 12 semanas. Todos los tipos de entrenamiento fueron beneficiosos para mejorar composición corporal y parámetros bioquímicos, el ejercicio de resistencia demuestra tener diferencia con relación a los otros dos protocolos de entrenamiento donde post-intervención consiguen mejorar la masa muscular. Debido al número pequeño de estudios aun la información es poco clara sobre cual protocolo es más efectivo y así poder elegir una alternativa mas adecuada. De acuerdo con los hallazgos realizar ejercicios aeróbicos y/o combinados mejoran la composición corporal a nivel de masa grasa, y el ejerciciode resistenciademuestra mejorar musculatura en adolescentes con obesidad.